Information management challenges for the Caribbean : keynote address - Carrington, Edwin W. (ACURIL San JuanPR, 1993)
Focuses on the challenges of the new information technologies for development. Looks at current efforts in the Region with respect to the harnessing of our information resources to enhance the development thrust. Identifies current regional initiatives and looks at the imperatives for training and education.